Literature Review: Identification of Dominant Factors in Patient Complaints in Health Services Reviewed from Service Quality Attributes - Candra Syah Putra; Aris Reko Utari; Bastoni Bastoni; Dara Puspita LT; Depi Lestari; Desi Ariani; Dewi Ratnadi; Dodi Iswahyudi; Joko Prayitno; Meliza Dian Putri; Nurrohimah Nurrohimah; Rapitariani Rapitariani; Raudah Raudah; Retno Megawati; Rohana Rohana; Yeni Andriani (Sean Institute, 2026)
Background: Healthcare services are currently facing increasingly fierce competition, where the success of a healthcare institution is not only measured by medical aspects, but also by its ability to satisfy patients. Research objective: To identify the healthcare service attributes that most frequently trigger patient complaints and dissatisfaction based on research results from various healthcare facilities (public hospitals, private hospitals, maternity hospitals, and community health centers). Method: Systematic review of 10 research articles using the Service Quality (SERVQUAL), Importance Performance Analysis (IPA), and Customer Satisfaction Index (CSI) methods. Results: Findings from 10 journals consistently show that the current quality of healthcare services is still below patient expectations (negative gap). The dominant factors that trigger complaints are divided into three main clusters: the responsiveness dimension, related to the speed of service and staff response; the empathy dimension, related to the interpersonal attitude and friendliness of staff, which is still considered low; and the physical evidence dimension, related to the maintenance of basic facilities such as sanitation and the comfort of the waiting room. Complaints related to staff behavior (unfriendliness) and slow procedures are the most frequent triggers of conflict in both inpatient and outpatient units. Conclusion: Patient satisfaction is highly dependent on the integration of technical quality (facilities) and functional quality (staff behavior). Healthcare facilities are advised to prioritize improving staff interpersonal communication skills and conducting regular audits of service waiting times to minimize potential complaints and increase patient loyalty.